The Future of Mountain Agriculture - Mann, Stefan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Mountain agriculture is a socially and culturally unique system, but also a regionally important economic sector. In a globalising world, it is clear that fertile areas on all continents will always be used to produce large quantities of agricultural products in order to feed the world and, increasingly, provide biomass as a source of energy. It is far less clear, however, how land use in steep and more peripheral regions will evolve. By definition, farmland in mountain areas is more difficult to work because of steep slopes and missing accessibility. Climate conditions and poor soil quality often add to these adverse conditions. Through overcoming limited views from one region only or from one discipline, this book intends to draw a first truly international perspective on the issue of mountain farming.
Introduction -- Land Use and Landscape Change in the Rockies: Implications for Mountain Agriculture -- Conservation Agriculture in the Andean Highlands: Promise and Precautions -- Enhancing crop diversity and livelihood security in the Andes through the emergence of agricultural innovation systems -- The future of agriculture in the High Atlas Mountains of Morocco: The need to integrate traditional ecological knowledge -- Climate Change and the future of Mountain Farming on Mt. Kilimanjaro -- Is mountain farming no longer viable? -- The complex dynamics of farming abandonment in the Pyrenees -- Future of Mountain agriculture in the Alps -- Food Security Challenges and Agricultural Development in Tajikistan -- Impact of natural resources and infrastructure on future livelihood in mountain farming in the Himalaya region.
Keywords: Geography; Regional planning; Agriculture; Sustainable development; Geography; Landscape/Regional and Urban Planning; Sustainable Development; Agriculture